Clinical Parameters of Silent Corticotroph Adenomas With Positive and Negative Adrenocorticotropic Hormone Immunostaining: A Large Retrospective Single-Center Study of 105 Cases - Zhang, Keyi; Shou, Xuefei; Chen, Hong; Qiao, Nidan; He, Wenqiang; Chen, Zhengyuan; Shen, Ming; Li, Shiqi; Zhao, Yao; Zhang, Zhaoyun; Li, Yiming; Ye, Hongying; et al. (Frontiers in Endocrinology, 2021)
Abstract Purpose: To investigate the different clinical characteristics of silent corticotroph adenomas (SCAs) with positive and negative adrenocorticotropic hormone (ACTH) immunostaining, and to explore the value of pituitary-restricted transcription factor (Tpit) immunostaining for diagnosing SCAs. Methods: The clinical materials of patients with SCAs who had a typical pathological feature with positive Tpit immunostaining and positive/negative ACTH immunostaining, and without clinical features and biochemical evidence for Cushing’s Syndrome in our center from Apr 2018 to Mar 2019 were analyzed retrospectively. The differences in clinical characteristics and surgical results between ACTH-positive and -negative SCAs were explored. Results: A total of one hundred and five patients (94.3% female) with SCAs were included. There were 66 SCAs with ACTH-negative (66/105, 62.9%), and 39 SCAs with ACTH-positive (39/105, 37.1%). Cases with ACTH-negative SCAs were more likely to have lower ACTH levels (27.5 ± 24.0 vs. 54.4 ± 58.6, P=0.011), more multiple microcysts (81.8% vs. 61.5%, P=0.022) and lower levels of Ki-67 expression (low expression rate 90.9% vs. 74.4%, P=0.023). No statistical significant differences were observed between patients with ACTH-positive and -negative SCAs regarding gender (97.0% vs. 89.7%, P=0.192), age (50.3 ± 10.3 vs. 49.0 ± 11.2, P=0.543), surgical history (16.7% vs. 23.1%, P=0.419), suprasellar extension (66.7% vs. 74.4%, P=0.408), sphenoid sinus extension (51.5% vs. 56.4%, P=0.627), cavernous sinus invasion (75.8% vs. 66.7%, P=0.314), large cyst on Magnetic Resonance Imaging (MRI) (47.0% vs 61.5%, P=0.149) or gross total resection rate (42.4% vs. 51.3%, P=0.379). Conclusions: ACTH-negative SCAs were observed to be more clinically silent and more likely to demonstrate multiple microcysts on MRI. The prevalence of SCAs, especially ACTH-negative SCAs, proved to be substantially underestimated and thus they should be given enough attention in consideration of the high aggressiveness of this subtype of refractory pituitary adenoma (PA).